Rola i miejsce edukacji zdrowotnej w programach nauczania łódzkich szkół licealnych - Szkudlarek, Agnieszka (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The article presents health education in the context of health issues as social values and the objective of the programme. The authors were trying to find out what is the opinion of youth and physical education teachers concerning school health education.Therefore, an attempt was made to present the current status of health education in secondary schools teaching programmes using the empirical studies that have been carried out among 100 pupils and 30 teachers of physical education in 5 secondary schools in Lodz. In the research process an opinion of respondents was regarded significant about the health education in the process of teaching, as well as their ratio to the health as values. On the basis of the analysis of the research results it is possible to notice, that opinion of girls and boys, as well as teachers of physical education on health concerns differ significantly from each other.The last part are the conclusions, which are at the same time, an attempt to present the role and place of health education in the school curricula of the tested schools.